DETERMINAN INTENSI MUZAKI DALAM MEMBAYAR ZAKAT MAL MELALUI LEMBAGA AMIL ZAKAT (LAZ) - Hanifa Dwi Safitri ; Achmad Zaky, MSA., Ak., SAS., CMA., CA (Akuntansi FEB - UB, 2018)
Indonesia has a huge potential for zakat, but the amount of zakat received is still small. Amil Zakat Institutions in Indonesia should be able to maximize the potential. Based on the problem, the researcher aimed to test the influence of attitude, subjective norms, perceived of behavior control, religiosity, and service quality to the intention in paying zakat on wealth through Amil Zakat Institutions. The method used in this research is survey method by distributing an online questionnaire to zakat payers (muzakki) who have paid zakat on wealth through Amil Zakat Institutions. Judgment sampling was used to determine the number of samples, because there is limited information about the population. Data was obtained for 90 samples and then analyzed with part least square (PLS) model by SmartPLS. The results of this study indicated that perceived of behavior control, religiosity, and service quality have a positive influence on the intention of paying zakat on wealth through Amil Zakat Institutions. However, attitudes and subjective norms do not have influence on that intention. Next, the results of this study are beneficial for Amil Zakat Institutions to evaluate their performance so that more people can utilize their services. Keyword: Religiosity, service quality, theory of planned behavior, zakat